The role of IL-6/JAK2/STAT3 signaling pathway in cancers - Huang, Bei; Lang, Xiaoling; Li, Xihong (Frontiers in Oncology, 2022)
Interleukin-6 (IL-6) is a pleiotropic cytokine involved in immune regulation. It can activate janus kinase 2 (JAK2)-signal transducer and activator of transcription 3 (STAT3) signaling pathway. As one of the important signal transduction pathways in cells, JAK2/STAT3 signaling pathway plays a critical role in cell proliferation and differentiation by affecting the activation state of downstream effector molecules. The activation of JAK2/STAT3 signaling pathway is involved in tumorigenesis and development. It contributes to the formation of tumor inflammatory microenvironment and is closely related to the occurrence and development of many human tumors. This article focuses on the relationship between IL-6/JAK2/STAT3 signaling pathway and liver cancer, breast cancer, colorectal cancer, gastric cancer, lung cancer, pancreatic cancer and ovarian cancer, hoping to provide references for the research of cancer treatment targeting key molecules in IL-6/JAK2/STAT3 signaling pathway.